"Far Back in American Time": Culture, Region, Nation, Appalachia, and the Geography of Voice. Issue 5 (3rd September 2018) - Revill, George; Gold, John R.
Abstract : This article develops a geography of voice to address the ways in which cultures, regions, and nations are imagined, figured, and defined. It adopts Connor's (2000) notion of vocalic space as a starting point from which to explore folk song collecting practices in Appalachia. It develops this in relation to Bauman and Briggs's (2003) postcolonial critique of the status of language and speech in ethnographic theory. Historically, the Appalachian region has received substantial ethnographic cultural study. Working with insights supplied by the collecting activities and subsequent writings of two key collectors—Cecil Sharp (1859–1924) and Alan Lomax (1915–2002)—this article offers a sociomaterial conception of voice key to its affective politics and examines historical theorizations. These are first derived from folklore and ethnography, later anthropology and sociology, and second, articulated with regard to geographies of region and nation. These are then considered in relation to geographer James Duncan's (1980, 1998) critique of the superorganic as an explanation of regional cultural distinctiveness. It concludes by arguing that a geography of voice can contribute to critical approaches to regionalism. An understanding of how vocalic spaces are figured and assembled is key to explaining how culture can be translated through levels of abstraction in ways that can marginalize and disenfranchise the very peoples given voice in regional studies of culture.